The Evolution of Skills in OECD Countries and the Role of Technology - Colecchia, Alessandra (OECD Publishing, 1996)
The aim of this paper is two-fold: to highlight stylised facts about recent trends in the skill distribution of employment and to analyse the role that technological change might have in explaining these dynamics. Data on industrial employment broken down by occupation recently assembled by the OECD Secretariat are used to examine the changing skill composition of OECD economies, the occupational structure of industry and services, and the dynamics of upskilling. They show that in most OECD countries during the 1980s, employment grew fastest in high-skilled jobs and slowest - or declined - in low-skilled jobs. The upskilling trend is more apparent in manufacturing than in services, while overall the shift to higher skilled jobs has occurred primarily within industries, rather than between them. Econometric work that explores the role of technology in the changing skill mix in five of the G7 countries in the 1980s shows that upskilling has occurred faster in industries that have ...
Keywords: Science and Technology